Coronavirus Proteins as Ion Channels: Current and Potential Research - McClenaghan, Conor; Hanson, Alex; Lee, Sun-Joo; Nichols, Colin G. (Frontiers in Immunology, 2020)
Coronavirus (CoV) outbreaks have recently emerged as a global public health threat due to their exceptional zoonotic potential – a feature arising from their ability to infect a diverse range of potential hosts combined with their high capacity for mutation and recombination. After Severe Acute Respiratory Syndrome (SARS) CoV-1 in 2003 and Middle East Respiratory Syndrome (MERS) CoV in 2012, with the current SARS-CoV-2 pandemic we are now in the midst of the third deadly international CoV outbreak in less than 20 years. Coronavirus outbreaks present a critical threat to global public health and an urgent necessity for therapeutic options. Here we critically examine the current evidence for ion channel activity in CoV proteins, and the potential for modulation as a therapeutic approach.